Preparation and characterization of manganese, cobalt and zinc DNA nanoflowers with tuneable morphology, DNA content and size. Issue 15 (12th July 2018) - Baker, Ysobel R; Chen, Jinfeng; Brown, Jason; El-Sagheer, Afaf H; Wiseman, Philip; Johnson, Errin; Goddard, Paul; Brown, Tom
Abstract: Recently reported DNA nanoflowers are an interesting class of organic-inorganic hybrid materials which are prepared using DNA polymerases. DNA nanoflowers combine the high surface area and scaffolding of inorganic Mg2 P2 O7 nanocrystals with the targeting properties of DNA, whilst adding enzymatic stability and enhanced cellular uptake. We have investigated conditions for chemically modifying the inorganic core of these nanoflowers through substitution of Mg 2+ with Mn 2+, Co 2+ or Zn 2+ and have characterized the resulting particles. These have a range of novel nanoarchitectures, retain the enzymatic stability of their magnesium counterparts and the Co 2+ and Mn 2+ DNA nanoflowers have added magnetic properties. We investigate conditions to control different morphologies, DNA content, hybridization properties, and size. Additionally, we show that DNA nanoflower production is not limited to Ф29 DNA polymerase and that the choice of polymerase can influence the DNA length within the constructs. We anticipate that the added control of structure, size and chemistry will enhance future applications.